1999
DOI: 10.1002/(sici)1098-108x(199903)25:2<223::aid-eat12>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the ideal of female beauty on mood and body satisfaction

Abstract: Objective The present study examined changes in women's mood states resulting from their viewing pictures in fashion magazines of models who represent a thin ideal. Method Female university students completed the Profile of Mood States (POMS), the Body Parts Satisfaction Scale (BPSS), and the Eating Disorder Inventory (EDI). They were then exposed to 20 slides; the experimental group (N = 51) viewed images of female fashion models and a control group (N = 67) viewed slides containing no human figures. All subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
2
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(72 citation statements)
references
References 6 publications
4
62
2
3
Order By: Relevance
“…They found a significant decrease in the model's body weights and measurements, with 70% of the women being underweight and more than 75% of the women were less than 85% of their ideal body weight. The research that has focused mainly on adolescent, media and body image (Pinhas & Toner et al, 1999;Tigemann & Pickering 1996;Meyers & Biocca 1992;Irving, 1990;Freedman 1984;Tan, 1977) examines the problematic effects of exposure to thin ideal media image on young women. Therefore, there is enough evidence to link relationship between thin ideal image portrayed in media and the development of eating disorder in adolescent females.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found a significant decrease in the model's body weights and measurements, with 70% of the women being underweight and more than 75% of the women were less than 85% of their ideal body weight. The research that has focused mainly on adolescent, media and body image (Pinhas & Toner et al, 1999;Tigemann & Pickering 1996;Meyers & Biocca 1992;Irving, 1990;Freedman 1984;Tan, 1977) examines the problematic effects of exposure to thin ideal media image on young women. Therefore, there is enough evidence to link relationship between thin ideal image portrayed in media and the development of eating disorder in adolescent females.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Randomized experiments more effectively rule out this possibility, although they can have limited external validity. Experiments have found that exposure to ultra-slender media images results in acute increases in body dissatisfaction and negative affect among young adult females (Cash, Cash, & Butters, 1983;Irving, 1990;Pinhas, Toner, Ali, Garfinkel, & Stuckless, 1999;Posavac, Posavac, & Weigel, 2001;Richins, 1991;Stice & Shaw, 1994). For example, one study found that a 3-minute exposure to thin-ideal images from a fashion magazine, compared with control images, resulted in increased depression, shame, guilt, stress, insecurity, and body dissatisfaction (Stice & Shaw, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Uma vez que o ideal de magreza proposto é uma impossibilidade biológica para a maioria das mulheres, a insatisfação corporal tem se tornado cada vez mais comum. 41 Assim sendo, o contexto sociocultural e os fatores que modulam seu impacto em cada indivíduo têm lugar assegurado na gênese dos TA. 40 O padrão de beleza veiculado pelos meios de comunicação e pelo convívio social parece exercer um efeito marcante sobre as mulheres.…”
unclassified